2009
DOI: 10.1051/ata/2009058
|View full text |Cite
|
Sign up to set email alerts
|

Driving under the effects of drugs of abuse: studies of oral fluid

Abstract: -Introduction:This study includes the evaluation of the use of drugs of abuse ratio in leisure environments, in order to determine which drugs are the most widely used, which are normally used in poly-consumption. Methods: Total sample rise to 216 cases which were collected on the road by traffic police and analyzed by an on-theroad driving test of possible consumption. Positive samples were confirmed by GC/MS-MS. Results: It was detected positive samples for the studied drugs (cocaine, heroin metabolites (6-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The best-known member of the ecstasy group of drugs is 3.4-methylenedioxy-methamphetamine (MDMA), but other analogues are also sometimes found in ecstasy tablets (3,4-Methylenedioxyamphetamine (MDA), MDEA). The drug is commonly used in social scenes such as dance events and is frequently combined with other drugs such as cannabis and amphetamines and (most frequently) alcohol (Brookhuis et al 2004 ; Nabben et al 2007 ; Mora et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The best-known member of the ecstasy group of drugs is 3.4-methylenedioxy-methamphetamine (MDMA), but other analogues are also sometimes found in ecstasy tablets (3,4-Methylenedioxyamphetamine (MDA), MDEA). The drug is commonly used in social scenes such as dance events and is frequently combined with other drugs such as cannabis and amphetamines and (most frequently) alcohol (Brookhuis et al 2004 ; Nabben et al 2007 ; Mora et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Statistical data related to drivers involved in fatal traffic accidents in Catalonia (Spain) demonstrated that 6.9% tested positive to the presence of drugs 6 and the prevalence of drugs of abuse found in OF of drivers in Catalonia has been reported before. 7 During 2007, the Generalitat de Catalonia carried out drug detection tests in OF of drivers 8 and obtained a positive result in two out of every three tests. The police set up their controls using an immunoassay Cozart DDS, taking the sample when impaired driving was observed.…”
Section: Introductionmentioning
confidence: 99%